1977
DOI: 10.1111/j.1440-1754.1977.tb01161.x
|View full text |Cite
|
Sign up to set email alerts
|

A Coronary Risk-Factor Profile of 4 Year Olds: Blood Pressure, Serum Lipids and Skinfold Thickness, in Normal Children

Abstract: Boulton, T. J. C. (1977). Aztst. F'aediatr. J., 13, 271-275. A coronary risk-factor profile of 4 year olds : Blood pressure, serum lipids and skinfold thickness in normal children. Anthropometric and biochemical data from a pilot-study of 65 four-year-old children is presented. The children in the study fell into the normal range for height, weight, fatness, blood pressure, and serum lipids. Within this normal sample, positive correlations were found between heightand fatness ( P < 0.02, r 0.27), height and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…If this lifestyle cannot be changed for a population, is it realistic and practical to identify those people who are at risk of early ill-health? If so, then these preventive measures may lie with paediatricians and the school health services.A preliminary study (Boulton, 1977) has shown that, in a minority of normal kindergarten children, positive associations were present between the systolic blood pressure, serum lipid levels, and…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If this lifestyle cannot be changed for a population, is it realistic and practical to identify those people who are at risk of early ill-health? If so, then these preventive measures may lie with paediatricians and the school health services.A preliminary study (Boulton, 1977) has shown that, in a minority of normal kindergarten children, positive associations were present between the systolic blood pressure, serum lipid levels, and…”
mentioning
confidence: 99%
“…A preliminary study (Boulton, 1977) has shown that, in a minority of normal kindergarten children, positive associations were present between the systolic blood pressure, serum lipid levels, and…”
mentioning
confidence: 99%